The good enough facilitator: exploring online interprofessional therapeutic facilitation in times of COVID-19. Issue 5 (2nd September 2020) - Bluteau, Patricia
ABSTRACT: In the time of COVID-19, universities have been forced to engage with online learning more than ever before. The facilitator is a key player in the orchestration of online learning and as such, this paper seeks to present a radical reworking of the Garrison and Archer Community of Inquiry model that emphasizes the importance of a therapeutic presence in online interprofessional facilitation. Drawn from a strand of inductive empirical qualitative research based on 15 years' experience of online interprofessional education, this paper employs a therapeutic lens to propose the good enough facilitator as a theoretical construct that emphasizes the importance of the facilitator understanding when to intervene and when to retreat within the online space. Online interprofessional asynchronous discussion groups are explored to illustrate the value of the good enough facilitator in online learning.